ECONOMIC REFORMS, FORMATION OF PRIVATE OWNERSHIP HISTORY OF THE DEVELOPMENT OF MARKET RELATIONS IN UZBEKISTAN - Nosirov Rashod Adilovich; Svetlana Vladimirovna Temirova (American Journals, 2023)
The article analyzes fundamental reforms in all spheres of life of our society during the years of independence, market economy, production, exchange and money circulation laws, economic system, history of stages of transition to market economy.
Keywords: Market economy, commodity production, exchange, law, history.